An interactive OOP learning environment for teaching and learning with Java / Wan Saiful 'Azzam Wan Ismai,Maznie Manaf and Marina Ahmad - Wan Ismail, Wan Saiful 'Azzam; Manaf, Maznie; Ahmad, Marina (2018)
Massive Open Online Courses (MOOCs) are said to be a form of online learning. MOOCs are a creature of the digital age and born of cloud computing. Millions of individuals have participated in thousands of these higher learning courses. The aims of MOOCs program to make the learning process are simple, easy, anywhere and anytime, and become the globalized online learning. The Object-Oriented Programming (OOP) is the subject for Diploma in Computer Science in MARA University of Technology (UiTM) which necessitate students to learn and apply the concepts of objects and classes, abstraction, encapsulation, inheritance and polymorphism. Students also learn on how to apply concept of OOP to store and retrieve data using text files. Teaching and learning quality of students in this course can be more interactive with MOOCs. In typical MOOC has specific topic to learn and discuss with incredibly large numbers of students and facilitators. The main elements used in these interactive learning is building an online system that provides an integrated environment for students doing programming activities and coursework; providing students with timely and useful feedback about programming activities without the need to have instructors and students meet at the same time and the same place.